Adaptation of Interpersonal Support Evaluation List (ISEL-12) for Mothers of Children Aged 3-6 Years in Indonesian Context - Hidayati, Fina; Hartini, Nurul; Chusairi, Achmad (Psikoislamika: Jurnal Psikologi Islam, 2024)
Adaptation of psychological instruments is very important because of differences in culture and context. This study aims to adapt the Interpersonal Support Evaluation List (ISEL-12) in an Indonesian context. Initial steps include back-to-back translation, focus group discussions, expert assessments, and pilot studies. From this procedure, the number of items obtained is 12 which is the original ISEL-12 version, there are five revised items according to the context of cultural groups and parenting activities of mothers with children of early child age (3-6 years). The twelve final questions were tested on 533 mothers with an average age of 34.5 years from several regions in Indonesia. Construct validity tests are performed using EFA and CFA. The analysis showed good validity and reliability (Cronbach's alpha: 0.920) and item loading factors ranging from 0.398-0.816 by showing that the three-factor model was suitable, with values based on RMSEA=0.079, CFI=0.923, TLI=0.911 and GFI=0.918. The conclusion is that ISEL-Ind also has 3 aspects in forming social support for mothers who have children in early childhood, namely, tangible support, belonging support and appraisal support. Keyword: Mother’s; Social Support; ISEL